Examining the Characteristics of Academic Entrepreneurs: The Case of Malaysian Technology Driven University - Ahamat, Amiruddin; Mohamad Sharif, Sabri; Shahkat Ali, Muhamad Sham; Masrom, Nor Ratna; Abdul Aziz, Che Nurul Azni (Journal of Technical Education and Training, 2020)
The aim of this study is to examine the various factors that lead technology researchers to recognise and create opportunities. The case study is derived from one of Malaysiaâ€™s technology driven universities. This research adopts a qualitative method in which the data were collected from nine lecturers and researchers who were actively involved in creating innovative products and services. Interviews and observational methods were employed with six of the respondents. The findings show that networking was used to get resources, and opportunities were from the policy or government interventions and events such as seminars and conferences. Most of the respondents say that events are great opportunities to connect with the industry and external parties. Hence, technology researchers can gain experience and opinions from the same or different fields. Through extensive networking, technology researchers can build various programs for new researchers so that they realize the importance of opportunities, especially in the field of technology, as it is now booming. The implication of this study reflects the universityâ€™s effort that can be viewed from the case, where self-efficacy and risk taking can be further promoted among academics who are moving from research to business venture. For the study to be conducted in the future, the researcher suggests the need to obtain a better understanding of conditions of uncertainty which shape opportunity creation and the scope of the research must be extended to other aspects. Future research should also include other institutions involving researchersâ€™ technologies to see clearly the role of opportunity creation and the challenges faced by them.